2012
DOI: 10.1051/0004-6361/201220240
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional hydrodynamical CO5BOLD model atmospheres of red giant stars

Abstract: Aims. We investigate the role of convection in the formation of atomic and molecular lines in the atmosphere of a red giant star. For this purpose we study the formation properties of spectral lines that belong to a number of astrophysically important tracer elements, including neutral and singly ionized atoms (Li Ba ii, and Eu ii), and molecules (CH, CO, C 2 , NH, CN, and OH).Methods. We focus our investigation on a prototypical red giant located close to the red giant branch (RGB) tip (T eff = 3660 K, log g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 18 publications
4
51
1
Order By: Relevance
“…This is, in particular, distinctive for low-excitation neutral iron lines as previously found by Asplund et al (1999) and Collet et al (2007). Kučinskas et al (2013) present similar findings for a solar-metallicity RG simulation as well, namely that neutral iron lines based on 1D MLT models are slightly closer to the full 3D lines compared to the 3D lines.…”
Section: Comparison With 1d Modelssupporting
confidence: 89%
See 1 more Smart Citation
“…This is, in particular, distinctive for low-excitation neutral iron lines as previously found by Asplund et al (1999) and Collet et al (2007). Kučinskas et al (2013) present similar findings for a solar-metallicity RG simulation as well, namely that neutral iron lines based on 1D MLT models are slightly closer to the full 3D lines compared to the 3D lines.…”
Section: Comparison With 1d Modelssupporting
confidence: 89%
“…Since their effect is strongest in convective zone below the optical surface and the line formation region, the influence in terms of abundance is likely small; in fact, Kučinskas et al (2013) only found a very small effect < 0.02 dex for the reduction in α MLT from 1.5 to 1.2. However, for metal-poor giants the influence can be greater for lines with very high excitation potential.…”
Section: Comparison With 1d Modelsmentioning
confidence: 86%
“…It has been established in previous works that deviations in line abundance exist between 3D and 1D analyses (Asplund et al 1999;Asplund & García Pérez 2001;Frebel et al 2008;Kučinskas et al 2013). The analysis done here likewise found abundance differences in the 3D analysis, relative to the 1D analysis in Paper I.…”
Section: D-1d Abundance Differencesmentioning
confidence: 94%
“…Kučinskas et al (2013) studied 3D vs. 3D effects for metal lines, but these results can not be applied to non-trace elements and saturated lines. In principle, the monochromatic flux would Fig.…”
Section: Model Spectramentioning
confidence: 99%